Global population structure, genomic diversity and carbohydrate fermentation characteristics of clonal complex 119 (CC119), an understudied Shiga toxin-producing E. coli (STEC) lineage including O165:H25 and O172:H25. Issue 3 (23rd March 2023) - Nakamura, Keiji; Seto, Kazuko; Lee, Kenichi; Ooka, Tadasuke; Gotoh, Yasuhiro; Taniguchi, Itsuki; Ogura, Yoshitoshi; Mainil, Jacques Georges; Piérard, Denis; Harada, Tetsuya; Etoh, Yoshiki; Ueda, Saori; et al.
Abstract : Among Shiga toxin (Stx)-producing Escherichia coli (STEC) strains of various serotypes, O157:H7 and five major non-O157 STEC (O26:H11, O111:H8, O103:H2, O121:H19 and O145:H28) can be selectively isolated by using tellurite-containing media. While human infections by O165:H25 STEC strains have been reported worldwide, their detection and isolation are not easy, as they are not resistant to tellurite. Systematic whole-genome sequencing (WGS) analyses have not yet been conducted. Here, we defined O165:H25 strains and their close relatives, including O172:H25 strains, as clonal complex 119 (CC119) and performed a global WGS analysis of the major lineage of CC119, called CC119 sensu stricto (CC119ss), by using 202 CC119ss strains, including 90 strains sequenced in this study. Detailed comparisons of 13 closed genomes, including 7 obtained in this study, and systematic analyses of Stx phage genomes in 50 strains covering the entire CC119ss lineage, were also conducted. These analyses revealed that the Stx2a phage, the locus of enterocyte effacement (LEE) encoding a type III secretion system (T3SS), many prophages encoding T3SS effectors, and the virulence plasmid were acquired by the common ancestor of CC119ss and have been stably maintained in this lineage, while unusual exchanges of Stx1a and Stx2c phages were found at a single integration site. Although the genome sequences of Stx2a phages were highly conserved, CC119ss strains exhibited notable variation in Stx2 production levels. Further analyses revealed the lack of SpLE1-like elements carrying the tellurite resistance genes in CC119ss and defects in rhamnose, sucrose, salicin and dulcitol fermentation. The genetic backgrounds underlying these defects were also clarified.